FUNCTIONS OF LEGAL CULTURE IN THE MODERN INFORMATION SPACE - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to clarify the role of legal culture and highlight the functions of legal culture in the modern information space. Research methods: general methods of thinking, functional, systemic, structural and synergetic. Results: it is proved that legal culture, exerting an active influence on people’s consciousness, is an important ideological tool in the establishment of legal values in the modern information space, serves as a means of ensuring human rights, preventing their restriction and implementation. The functions of legal culture are distinguished: cognitive-legal-educational, value-normative, communicative, legal-socialization, preventive, ideological-educational, prognostic. Discussion: it is established that the main problems with ensuring human rights in the modern information space in a pandemic are imperfect information policy of the state, gaps in legislation, lack of involvement of civil society in communication; Restrictions on individual human rights for the protection of public health in a pandemic must comply with international and national human rights standards. In the current conditions of the COVID-2019 pandemic, the problem of legal culture, in particular, public awareness of rights, features of their implementation and protection should play an important role in overcoming coronavirus disease. In the rapid development of the information society, the adoption of new legislation, the transition to the introduction of information and communication technologies in all spheres of public life, the analysis of the functions of legal culture in the modern information space becomes important. Citizens must be aware of their rights, have unhindered access to information, and know how to protect their rights, particularly in a pandemic. In today’s information space, it is particularly important that human rights are an integral part of all measures to combat the COVID-19 pandemic. It is important that in the modern information space equal opportunities are created for all its subjects, shortcomings are eliminated, the mechanism of realization and protection of human rights is provided.